Demograficzne korzenie i perspektywy statystyki małych obszarów - Gołata, Elżbieta; Paradysz, Jan (Demographic Roots and Perspectives of Small Area Statistics, 2007)
Small area estimation is becoming important in survey sampling due to a growing demand for reliable small area statistics from both public and private sectors. The paper refers to demographic background of small area estimation SAE, its determinants, applications and perspectives. Usually the demographic origin of SAE is restricted to methods for local estimation of population in post-censual years. That is why demographics contribution in the development of SAE techniques is presented according to the classification by J.N.K. Rao and the one used by UN experts in demographic research. The studies conducted by Polish demographers are described and own classification of SAE methods in demography, combining the two above mentioned as well as own experience is proposed. The present article is largely an appraisal of some of the methods. Among others we focus on E. Arriaga, G. Feeney and L. Henry methods for fertility estimation. Underlining the impact of demography in SAE studies we tried to mention the most important directions of further development. First of all, estimation methodology, data mining and integration of electronic data bases are considered. Special attention is focused on integration of administration records and survey studies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 89-108